Optimalisasi Kemasan Produk Untuk Memperkuat Minat Pasar dan Brand UMKM Lokal Desa Mekarmukti Bandung Barat - Bambang Suprayogi; Abdur Razak (Darma Abdi Karya, 2024)
The product packaging and brand of the local UMKM in Mekarmukti Cihampelas Village, West Bandung Regency has a big influence on the customer's perspective in choosing products, and with the implementation of the digital economy, this can help business income and if this business runs well, it can continue to increase the income of the Village's Local UMKM. Mekarmukti Cihampelas, West Bandung Regency. The role of the Digital Economy in terms of product packaging and branding in local UMKM in Mekarmukti Cihampelas Village, West Bandung Regency, simplifies the sales process, facilitates payment transactions and helps product marketing. Specifically for UMKM in this research, the local UMKM in Mekarmukti Cihampelas Village, Bandung Regency, are not yet economically independent and are not yet effective in using technology in managing and marketing products. Local UMKM in Mekarmukti Cihampelas Village, West Bandung Regency are still limited.